Propofol and postoperative infections - Bach, Alfons; Geiss, Heinrich K. (The New England journal of medicine, 1995)
To the Editor: Bennett et al.1 report on thorough investigations into postoperative infections associated with the use of the intravenous anesthetic propofol, but we would like to add some comments. Clusters of fever episodes, infections, or sepsis associated with propofol use were reported exclusively in the United States shortly after the approval of this drug by the Food and Drug Administration. Epidemiologic studies conducted subsequently implicated extrinsic contamination of propofol infusions with various microorganisms.2 Although the epidemiologic data constitute convincing indirect evidence that the infectious episodes stemmed from contamination of propofol through the improper use of aseptic techniques, in no . . .
Gesehen am 27.11.2023